Peran Konten Visual Instagram terhadap Niat Beli Pengguna melalui Ketersediaan Informasi Produk - Astika Ulfah Izzati; Markoni; Frianka Anindea (Asosiasi Ahli Administrasi Indonesia, 2024)
This study aims to examine the direct effect of visual of Instagram content and purchase intention, examine the influece between product information availability and purchased intention, and examine the influence of Instagram visual content to customers purchased intention through product information availability. This research used quantitative approach with causality analysis. By using two types and sources of data, namely primary data and secondary data. The data collection method is carried out directly on people who have used Instagram for shopping. The sample in this study was taken from a population that is considered representative which is 156 respondents. Statistical analysis used to test the mediating effect of product information availability in the relationship between Instagram visual content and purchase intention uses PROCESS MACRO Mediation by Hayes analysis. The result shows that visual of Instagram content indirectly and significantly influence purchase intentions through product information availability, and there is partial mediation in the relationship between visual of Instagram content and purchase intention through product information availability.